Depresión en adolescentes con consumo de alcohol - Baldeón Vivanco, Dayana Mariví (2024)
The aim of this research was to describe the scientific evidence on the relationship between depression and alcohol consumption in adolescents. This research is quantitative, nonexperimental, cross-sectional, descriptive, the data were collected from the platform Dialnet, Elsevier, Scielo, Science Direct, Springer Open, Redalyc through search engines such as: Google Scholar, Pubmed and Scopus, in order to obtain a more holistic and multifaceted view of the subject from the different inquiries and theories studied thanks to the Prisma program. This exploration contains the basic concepts such as: depression and alcohol consumption in adolescents, where a significant relationship was observed in these two variables. With the results obtained, it became evident that on average alcohol consumption occurs in 50.96% of adolescents with a greater predominance of the male sex with 33.19%. On the other hand, with regard to age, alcohol consumption among young people is between 14-15 years of age with 43.06%. Similarly, it is shown that adolescents maintain a low average level of depression with 42.56%, which shows that the young people did not present depressive states, followed by a medium level with 36.01% and, to a lesser extent, a high level with an average value of 21.43%. Finally, it is concluded that this study provided a broad and detailed approach to the relationship between depression and alcohol consumption in adolescents, highlighting the need for general approaches to mental health care in this population group, and also emphasized the importance of interventions to address depression and alcohol consumption in adolescents